2006
DOI: 10.1590/s0100-39842006000300014
|View full text |Cite
|
Sign up to set email alerts
|

O papel das variantes anatômicas do complexo ostiomeatal na rinossinusite crônica

Abstract: Currently, computed tomography is the method of choice for assessment of paranasal sinuses, nasal fossae and their anatomical variants. Presumably, these variations might induce osteal obstruction, preventing mucus drainage and predisposing to chronic rhinosinusitis. However, this concept is still controversial and the presence of any anatomical variant does not necessarily establish an etiology for rhinosinusitis. Among three subtypes of concha bullosa, only the bulbous type seems to be strongly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Paradoks konka infundibulumda kompresyon ve sinüs obstrüksiyonuna neden olabilir (16) . Çok büyük ve diğer anatomik varyasyonlarla birlikte olması durumunda sinüzit etyolojisinde önemli olabileceği kabul edilir.…”
Section: Discussionunclassified
“…Paradoks konka infundibulumda kompresyon ve sinüs obstrüksiyonuna neden olabilir (16) . Çok büyük ve diğer anatomik varyasyonlarla birlikte olması durumunda sinüzit etyolojisinde önemli olabileceği kabul edilir.…”
Section: Discussionunclassified
“…Different surveys studied miscellaneous patient groups varying in age, diseases, or for example ethnic groups [ 43 ], [ 46 ]. Some authors concluded that anatomical variations of the paranasal sinuses are progressively acquired with maturity [ 7 ]. We were not able to confirm or refute this conclusion due to the small sample size in our study, especially in terms of younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date it is not known whether Haller cells develop during the embryonic period or later in life [ 7 ], [ 8 ]. Chimpanzees and possibly orang-utans show pneumatization in the ethmoid bone similar to humans, perhaps due to their upright posture.…”
Section: Introductionmentioning
confidence: 99%
“…The paranasal sinuses begin to develop during the fetal period, in the third week of gestation, as invagination of the nasal mucosa into the lateral nasal wall, maxillae, frontal, ethmoid and sphenoid bones [1]- [3]. The maxillary sinus is the first sinus to develop; at birth, it is filled with fluid and becomes pneumatized [4]. The maxillary sinus can present anatomical variations such as pneumatization, antral septa, hypoplasia and exostosis [5].…”
Section: Case Reportmentioning
confidence: 99%